Challenges facing Primary School Head Teachers preparedness in Management of Free Primary Education in Siaya County, Kenya - Haruni, Hellen; Odera, Florence Y. (IJRDO- Journal of Educational Research, 2016)
The aim of free primary education (FPE) was to provide more school opportunities for all children. In pursuit of this policy objective, the government of Kenya introduced FPE in January 2003, resulting to increased enrolment from 5.9 million in 2002 to 7.2 million in 2004. This led to extra administrative duties for head teachers and continued administrative challenges in management of FPE programme related to lack of clear policy framework, management skills, interpretation of government policies. The purpose of this study was to identify challenges facing primary school headteachers in management of FPE, with the following specific objectives; to establish head teachers preparedness in management of FPE in Siaya sub-county, to identify training required by head teachers to manage FPE and to assess stake holders participation in management of FPE in Siaya sub-county. The study employed descriptive survey design. Population consisted of 130 public primary school head teachers, one sub county auditor and one sub quantity assurance and standard officer (SCQASO). Stratified sampling technique was used to obtain a sample of 43 public primary schools. Questionnaire, in-depth interview and observation schedule was used for data collection. Quantitative data was analyzed by use of descriptive statistics, frequencies, percentages, pie charts and graph, while contact analysis was used to analyze qualitative data. The findings established that head teachers were not adequately prepared to manage FPE, headteachers also needed to be equipped with management skills to effectively manage FPE. Lastly, stakeholders did not fully support management of FPE. Based on the findings, it was recommended that head teachers should extensively be trained in management of FPE, Quality assurance and standards officers and auditors should be financially empowered to train head teachers on management of FPE and stakeholders should be trained in their role in management of FPE.